Peran Mahasiswa Kkn Dalam Penguatan Tradisi Keagamaan: Implementasi Lomba 1 Muharram Di Desa Cahaya Negeri - Neli Julita; Yuni Yuliana; Okti Rere Purwanti; Khatitan; Qeisya Dwi Alparin; Melica Maharani; Andika Rahman; Riska Mardiyanti; Arum Mutiara Sari; Egi Satriyo; Nova Asvio (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) is a form of student service to the community that aims to integrate the implementation of the Tri Dharma of Higher Education with direct experience in the field. This research focuses on the role of KKN students in strengthening religious traditions through the implementation of the 1 Muharram Competition in Cahaya Negeri Village. Through a qualitative approach with a case study method, this research examines the contribution of KKN students in facilitating and mobilizing the community to preserve religious traditions that are increasingly threatened by modernization. The results show that KKN students play a significant role in introducing new approaches, motivating community participation, and raising awareness of the importance of religious traditions. However, there are challenges such as time constraints and resistance from some villagers to the innovations introduced. This study recommends strengthening the KKN program with a focus on preserving religious traditions and developing a more flexible duration and format of activities to have a more optimal impact on the community.